Dificultad, fracaso y negatividad en el canto noveno de la Ilíada - Míguez Barciela, Aida (Revista de Filosofía, 2007)
Book ninth constitutes a shift in the structure of the Iliad; Achilles is outlined as the figure capable of a knowledge which achieves nothing and leads to nowhere; but that turns out to be essential for the task of the Acheans’ community. The subject of the poem, the wrath of Achilles, shows itself as the distance from which the global horizon appears in some way; however, by being global distance it is also insolence, that is to say, distance-that-breaks-it-self.